2015
DOI: 10.1111/tmi.12641
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immune responses to a killed bivalent whole cell oral cholera vaccine between endemic and less endemic settings

Abstract: SummaryStudies on safety, immunogenicity and efficacy of the killed, bivalent whole cell oral cholera vaccine (Shanchol) have been conducted in historically endemic settings of Asia. Recent cholera vaccination campaigns in Haiti and Guinea have also demonstrated favourable immunogenicity and effectiveness in nonendemic outbreak settings. We performed a secondary analysis, comparing immune responses of Shanchol from two randomised controlled trials performed in an endemic and a less endemic area (Addis Ababa) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In the present study, we found IgA, IgG, and IgM plasma antibody responses to Ogawa OSP after the first dose of OCV, but again, there was no immunological boosting after the second dose of vaccine. This failure to give immunologic boosting with an OCV at 14 days after the first dose is similar to previous studies that suggested a 14 day interval may be too short to boost immune responses in vaccine recipients in cholera endemic areas [36, 37, 47].…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we found IgA, IgG, and IgM plasma antibody responses to Ogawa OSP after the first dose of OCV, but again, there was no immunological boosting after the second dose of vaccine. This failure to give immunologic boosting with an OCV at 14 days after the first dose is similar to previous studies that suggested a 14 day interval may be too short to boost immune responses in vaccine recipients in cholera endemic areas [36, 37, 47].…”
Section: Discussionsupporting
confidence: 88%
“…Killed whole-cell oral cholera vaccines (kOCVs) are now becoming part of the standard cholera control and prevention toolkit, in addition to the established water, sanitation, and hygiene interventions, surveillance, and case management. 1 Although kOCVs have been used across multiple settings and have been shown to be safe and immunogenic, 2 , 3 , 4 effectiveness and efficacy studies have provided a wide range of effect estimates, 5 , 6 , 7 , 8 , 9 hindering clear communication to policy makers and clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Due to differences in methodology, the GMF rise (and related measures) may be the most practical parameter for comparison since it is a relative measure that is less affected by interlaboratory variability. Aside from differences in assay procedures, age and baseline titers in endemic and nonendemic locations may influence the immune response to OCV, as has been noted previously [ 29 ]. The relatively high proportion of variance in first-dose seroconversion explained by heterogeneity between studies as opposed to within study sampling variance, or I 2 , is likely a result of these differences between settings and laboratory methods.…”
Section: Discussionmentioning
confidence: 99%